Pobreza urbana em Feira de Santana uma análise multidimensional - Filho, José Caetano de Jesus (2017)
Faced with the transformation’s processes of the Brazilian economy, especially the policies that aimed at industrialization from the 1930s, and more intensely from the 1950s, the issue of urban poverty emerges as problematic in the country. At 1970s, the policies of trade integration and the productive deconcentration, whose made advance upon the national territory the typical productive dynamics of capitalism, it had expanded the urban network in the states, that, underwent a later industrialization. Added to this are the regional development policies and the growth of medium-sized cities, that became like knots of the urban web, assuming regional importance. In this scenario, Feira de Santana went through an accelerated process of population and economic growth, entailing the constitution of an urban scenario full of contradictions. Faced of this process, the present work deals with the theme of Urban Poverty in Feira de Santana, having as aim understanding better its characteristics and analyzing its spatial distribution in the territory of the municipality, especially in the area of the city. For this purpose, the Multidimensional Poverty Index (MPI) was applied with aggregation within the census tracts, which allows the observation of the results at a smaller level than the neighborhood, making it possible to observe the contrasts of poverty inside and in the whole the urban area. The results obtained with the IPM, besides indicating the areas of concentration of greater poverty, was analyzed by the light of the formulations on the "pattern" of urbanization in dependent countries which present specificities in this process. In this way, it was possible to observe that the areas of concentration of poverty in the city of Feira de Santana are located in the most distant regions of the city center, taking the Anel de Contorno as a limit to be observed among the areas with the highest poverty index, since the census tracts with the highest level of deprivation in the analyzed baseline indicators and in the MPI are located in the area outside of that Anel. These results indicate a tendency that corroborates with the formulations about the process of urbanization in dependent countries, which points to a process of removal of the poorest population from the central areas, forming a peripheralization effect